MAINTENANCE OF TIME STANDARDS IN THE DEPARTMENT OF REFERENCE STANDARDS IN ZIELONKA. CONTRIBUTION INTO THE CREATION OF THE POLISH ATOMIC TIME SCALE TA (PL) - Gosztyła, Marcin (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
The article includes information about time standards in the Department of Reference Standards in Zielonka. The department is part of the Central Military Calibration Laboratory, which performs tasks related to the calibration standards of the other military calibration laboratories in Poland. The first part discusses components of a time standards station, which is involved in the creation of an Independent Polish Atomic Time Scale TA (PL), and its maintenance process. The second part is related to the analysis of the benefits of the inclusion of standard time calibration laboratory into the TA (PL). Last part presents the method of determining the parameters of the Relative Frequency Deviation (RFD), the prediction and uncertainly estimate of RFD.